Effects of 6-Week Interval Aerobic Training (IAT) and Nano-Selenium Supplementation on Laminin α5 and Collagen IV Expression in the Extracellular Matrix of Alveolar Epithelial Cells in the Lungs of Healthy and Cigarette Smoke-Exposed Rats - Ghaeni, Mansoureh; Mirdar, Shadmehr (International Journal of Sport Studies for Health, 2024)
Objective: This study aimed to investigate the effects of six weeks of interval aerobic training (IAT) and nano-selenium supplementation on laminin α5 and collagen IV expression in the extracellular matrix of alveolar epithelial cells in the lungs of cigarette smoke-exposed rats.Methods and Materials: This experimental laboratory study used thirty-five male Wistar rats weighing 180-220 grams. The rats were randomly divided into seven groups: Healthy control, COPD control, COPD IAT, Healthy IAT, Healthy Selenium, Healthy Selenium-IAT, and COPD Selenium-IAT. Cigarette smoke extract was used to induce lung injury. Nano-selenium particles were administered via gavage. Interval aerobic training was performed for six weeks, five days per week. The expression of laminin α5 and collagen IV in the extracellular matrix of alveolar epithelial cells was evaluated. Data were analyzed using the Shapiro-Wilk test, two-way ANOVA, and Tukey's post hoc test.Findings: Two-way ANOVA showed a significant difference in laminin α5 expression between the healthy control and COPD control groups (P=0.011), but no significant difference for collagen IV (P=0.971). There was also a significant difference in laminin α5 expression between the COPD control and COPD + IAT groups (P=0.011), but no significant difference for collagen IV (P=0.999). No significant differences in laminin α5 and collagen IV expression were found between the control and training or supplementation groups (P=0.999).Conclusion: The results suggest that six weeks of interval aerobic training may be beneficial for mitigating the negative effects of cigarette smoke on laminin α5 expression in the lungs of rats with induced COPD.